Fuzzy analytical hierarchy process for evaluating factors influencing Covid-19 vaccine acceptance / Norpah Mahat, Siti Sarah Raseli and Nur Izyan Nabilah - Mahat, Norpah; Raseli, Siti Sarah; Nabilah, Nur Izyan (Universiti Teknologi MARA, Perak, 2023)
The global Covid-19 pandemic originated in China and has rapidly spread to over 180 countries, infecting millions of people. As vaccination efforts are underway worldwide, Malaysia has administered booster doses, but many Malaysians have yet to sign up for the Covid-19 vaccine. This study aims to identify the factors that influence the acceptance of the Covid-19 vaccine in Malaysia and formulate a model to rank these factors. Pearson correlation analysis was used to assess the relationship between variables. Additionally, the Fuzzy Analytical Hierarchy Process (FAHP) method was employed to rank the factors. Results from Pearson correlation analysis revealed that confidence in the safety and effectiveness of the vaccine was the most significant factor influencing vaccine acceptance, followed by education level, media messages, convenience, and religion. FAHP results also showed that confidence in vaccine safety and effectiveness was the top-ranking factor with the highest weight value, followed by education, media messages, convenience, and religion. This research contributes to the understanding of the factors influencing Covid-19 vaccine acceptance in Malaysia and provides valuable insights for decision-makers to improve vaccine distribution strategies.